DISTRIBUSI BANGUNAN ARSITEKUR CINA DI KLASTER BALEKAMBANG KAMPUNG PECINAN KOTA SEMARANG - Anindya Puspita Putri; Henki Riko Pratama; Deny Setya Afriyanto; Tiyas Adhi Putra (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2023)
Law No. 11 of 2010 concerning Cultural Heritage states that preservation is a dynamic effort to maintain the existence of Cultural Heritage and its value by protecting, developing, and utilizing it. Starting from this, in other words, preservation is an effort to ensure that a cultural work remains or returns to a living cultural context, through a process of reuse, recycling, and revitalization. One of the Cultural Heritage Areas in the City of Semarang which has important value and is urgently required to be given protection is the Semarang Chinatown Area. The next step is related to the process of preserving (protecting) the Chinatown area of Semarang City. It is necessary to carry out a study to inventory ancient buildings that have a uniform Chinese architectural style and have important value. It is hoped that this study can be used for recreational, educational, appreciative, and/or religious purposes. This is in accordance with what is mandated by Law 11 of 2010 concerning Cultural Heritage, which states that the determination of area and layout is determined based on the results of studies by prioritizing opportunities to improve people's welfare. Keywords:. Cultural Heritage Preservation, Urban Heritage, Mapping, Chinatown